How project finance can advance the clean energy transition in developing countries - Robin Baker; Philippe Benoit (The Oxford Institute for Energy Studies, 2022)
The global climate change imperative presents a particular challenge because of the scale and nature of the investment needed in developing countries, coupled with the difficulty of raising long term debt in many of them. Project finance can help to address this challenge because it enables separation and allocation of different risks to different parties, which can help to attract different funders with different risk appetites. In particular, it is a vehicle to segregate green assets for funding and could assist in incorporating targeted credit enhancement products, such as those offered by the World Bank and other governmental agencies looking to promote clean energy investments. This international dimension is critical, as the challenge will require substantial outside support and innovation. The constraint is not the global availability of finance, but the risk profile of the projects (mostly local-currency generating projects with longer-term infrastructure-type returns) and the availability of the necessary skilled resources. Unless addressed, these constraints will continue to limit the availability of debt finance for clean energy projects in developing countries and thus the ability to achieve global climate change objectives.
Keywords: 330; debt; developing world; Energy Transition; green finance; multilateral lending; project finance